Peran Negara Donor dan Organisasi Internasional Melalui InaTEWS dalam Disaster Risk Reduction di Indonesia - Hapsari, Dorothea Ratri Parama; Farabi, Nadia (International Relations, Faculty of Social and Political Sciences, Universitas Diponegoro, 2020)
This study discusses the role of donor countries and international organizations through InaTEWS (Indonesia Tsunami Early Warning System) in Disaster Risk Reduction to fulfill the economic security of the Indonesian people. InaTEWS is a tsunami early warning system in Indonesia, which is expected to reduce the risk of tsunamis, for the sake of achieving human security. The huge losses in the 2004 tsunami tragedy that struck Aceh and neighboring countries became a starting point for supporting the development of a tsunami in the Indian Ocean region. Germany and various donor countries and other international organizations provide development assistance and development for InaTEWS. This research uses the concept of human security to explain the basic human needs of